Flouting Maxim in Wednesday Series - Mawarni, Titis; Wibowo, Agung Prasetyo (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
Flouting maxim is happened when the speakers blatantly fail to follow the cooperative principles and convey the meaning to the listeners. The objectives of this research are to find out the types of flouting maxim in Wednesday series and to identify the type of flouting maxim that most frequently used in Wednesday series used Grice (1975) theory. This research used descriptive qualitative method. The result showed that the researcher found 4 types of flouting maxim, they were flouting maxim of quantity for 40 (38%) data, flouting maxim of quality for 23 (22%) data, flouting maxim of relation for 21 (20%) data, and flouting maxim of manner for 21 (20%) data. The dominant flouting maxim frequently occurred in the Wednesday series is the flouting maxim of quantity for 40 (38%) data.